Evaluation of resistance training equipment using three dimensional musculoskeletal modelling focusing on the biomechanical and anthropometric considerations of the enduser - Els, P.S. (Pieter Schalk) (University of Pretoria, 2013)
Thesis (DPhil)--University of Pretoria, 2011.